P726Coronary NET burden and DNase activity in ST-elevation acute coronary syndrome are predictors of infarct size. (15th July 2014) - Mangold, A; Scherz, T; Alias, S; Hofbauer, T; Jakowitsch, J; Bangert, C; Pfaffenberger, S; Winter, MP; Preissner, KT; Lang, IM
Abstract: Background: Mechanisms of coronary occlusion in ST-elevation acute coronary syndrome (STE-ACS) are poorly understood. We have previously reported accumulation of neutrophils (polymorphonuclear cells [PMNs]) in culprit lesion site thrombi. The goal of the present study was to quantify PMNs, their formation of neutrophil extracellular traps (NETs), and to examine the relationships of extracellular DNA, DNase and clinical outcomes. Methods and Results: We analyzed coronary thrombectomy aspirates from 112 patients undergoing primary percutaneous coronary intervention. Compared to systemic PMNs, coronary thrombus PMNs were characterized by high expression of activation markers and by the formation of aggregates with platelets. Nucleosomes, neutrophil elastase, myeloperoxidase and myeloid-related protein 8/14 were increased in coronary plasma, and NETs significantly contributed to the scaffolds of particulate coronary thrombi. Thrombus NET burden was directly correlated with infarct size, while culprit site DNase activity showed a reverse correlation with infarct size. Recombinant DNase accelerated lysis of coronary thrombi ex vivo. Conclusion: PMNs are highly activated in STE-ACS and undergo NETosis at the culprit lesion site. Coronary NET burden and DNase activity are predictors of myocardial infarct size.